EFFECTS OF WORK CULTURE, ORGANIZATION LEARNING, AND SELF EFFICACY TOWARDS THE WORK EFFECTIVENESS OF THE LECTURERS AT POLITEKNIK KESEHATAN KEMENKES RI TANJUNGKARANG - Masra, Ferizal; Akbar, Ma’ruf; Fuad, Nurharttati (Journal of Education Research in Administration and Management (JERAM), 2018)
The purpose of this research is to know the impact of work culture, organizational learning, and self efficacy to the effectiveness of lecturers' work at Politeknik Kesehatan Kemenkes RI Tanjungkarang. This research uses the quantitative survey method and conducted to the lecturers of Politeknik Kesehatan Kemenkes RI Tanjungkarang with 99 people taken as samples. The data was collected using questionnaires and analyzed using the path analysis. The results of this study show that work culture, organizational learning, and self efficacy have a direct positive effect on work effectiveness; work culture and organizational learning have a direct positive effect on self efficacy; and work culture has a direct positive effect on organizational learning.   Keywords: Work Effectiveness, Work Culture, Organizational Learning, and Self Efficacy.